2011
DOI: 10.2527/jas.2010-3435
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior and performance of lambs are influenced by flavor diversity1,2

Abstract: This study determined whether early experiences of sheep with the same feed, but presented in multiple or single flavors, would influence intake, the profile of hormones involved in feed intake regulation, and the subsequent acceptability of novel feeds. Thirty-five 2-mo-old lambs were randomly assigned to 5 treatments (7 lambs/treatment). Lambs in 1 treatment (the diversity treatment) were simultaneously fed an unflavored plain ration of alfalfa (control) and barley (75:25; as-fed basis) and the same ration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 50 publications
4
30
1
1
Order By: Relevance
“…TMR-fed lambs consumed less total dry matter (P<0.05), metabolizable energy (P<0.01), soybean meal (P<0.01), corn (P<0.01) and crude protein (P<0.01) than FCF-fed lambs whereas FCF-fed lambs consumed less alfalfa hay (P<0.01), barley (P<0.05), wheat bran (P<0.01) and energy to protein ratio (P<0.01) than TMR-fed lambs (Table 2). Because growing ruminants have greater needs for nutrients, especially protein (Villalba et al, 2011), it is likely that this effect enhanced intake of dry matter and protein in the FCF system relative to that in the TMR system. These findings support the idea that lambs offered a choice among an option of feeds (ground barley, cottonseed meal, wheat bran and alfalfa hay) successfully regulated their nutrient intakes and attained better growth performance (Görgülü et al, 1996;Dikmen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…TMR-fed lambs consumed less total dry matter (P<0.05), metabolizable energy (P<0.01), soybean meal (P<0.01), corn (P<0.01) and crude protein (P<0.01) than FCF-fed lambs whereas FCF-fed lambs consumed less alfalfa hay (P<0.01), barley (P<0.05), wheat bran (P<0.01) and energy to protein ratio (P<0.01) than TMR-fed lambs (Table 2). Because growing ruminants have greater needs for nutrients, especially protein (Villalba et al, 2011), it is likely that this effect enhanced intake of dry matter and protein in the FCF system relative to that in the TMR system. These findings support the idea that lambs offered a choice among an option of feeds (ground barley, cottonseed meal, wheat bran and alfalfa hay) successfully regulated their nutrient intakes and attained better growth performance (Görgülü et al, 1996;Dikmen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The umami taste, induced by monosodium glutamate, is perceived by sheep since (i) it increased intake of sham-fed animals (Colucci and Grovum, 1993) and (ii) it induced preferences when added to hay compared with the same untreated hay (Gherardi and Black, 1991). Recent studies, using either a non-caloric flavour or monosodium glutamate to induce the umami taste, showed that lambs are able to perceive umami taste in a feed, as they increased their preference for this feed (Favreau et al, 2010a;Villalba et al, 2011;Bach et al, 2012).…”
Section: Sensory Characteristics In Feeding Behaviourmentioning
confidence: 99%
“…Sheep preferred to eat a varied array of plant species and feeds (Provenza, 1996;Villalba et al, 2011) or feeds offered in different fl avors (Scott and Provenza, 1998). This is so, in part, because a diverse diet most likely satisfi ed multiple nutrient requirements (Simpson et al, 2004).…”
Section: Ecological Importance Of Experience With Diverse Feeds Earlymentioning
confidence: 99%
“…In our study, lambs showed a greater intake of soybean meal (high proportion of RDP) than corn gluten meal (low proportion of RDP; NRC, 1985). In addition, growing ruminants displayed clear preferences for protein-rich feeds and fl avors that signal protein (e.g., umami), as their requirement for protein is high (Villalba et al, 2011). Finally, nutrient requirements were established for the "average animal" under conditions imposed by animal production systems; therefore, the biological goals of individual lambs selecting a diet may lead to a dietary balance different from that expected (Atwood et al, 2001;James et al, 2002).…”
Section: Dietary Monotony Feed Diversity and Diversity With Plant Tmentioning
confidence: 99%